نەرگسیەت یان خود لە شیعرى لەتیف هەڵمەتدا - حسین, علي طاهر (Sulaimani Journal for Humanities, 2002)
The bioiogical side and narissism of the Kurdish poet latif Halmat is the main core of the thesis, which cleariy appears in his usage of the persoual pronoun “T” in this poetical works. The Research depends on various references, some of them are psychological books while others are concerned with pure literature. The study deals with the definition of the term narissism, then attention is given to the different point of views repesented about the term, Further more, we didn't try to appiy narissism on the selected texts, as a psychic may do, instead we tried to shed some light on the effect of narissism on the poet since we believe the work is critical and literal in the first stage beside our study of the psychological side.